2019
DOI: 10.1080/02615479.2019.1591361
|View full text |Cite
|
Sign up to set email alerts
|

Talking about emotion: how are conversations about emotion enabled in the context of social work practice education?

Abstract: It is widely acknowledged that emotion is a potent force in social work practice and practice education which can have a significant impact on both practice and practitioner experience.So too, is the recognition that social work students may face higher levels of stress than their qualified colleagues -social work itself, one of the professions where workers often experience higher levels of emotional demand than do other occupational groups. In terms of professional training courses for students entering the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 34 publications
0
5
0
4
Order By: Relevance
“…El entrenamiento en IE debe ser considerado como un elemento transversal en todas las materias de la formación en Trabajo Social. Por ejemplo, las conversaciones sobre las emociones entre estudiantes y profesionales de Trabajo Social con funciones de tutorización de prácticas son una excelente oportunidad pedagógica para la comprensión de los estados emocionales tanto propios como ajenos (i.e., usuarios, compañeros, supervisoras...), la disminución de la sensación de vulnerabilidad y la potenciación del crecimiento profesional y de la felicidad subjetiva (Dore, 2019). Paralelamente, otra línea de actuación se podría centrar en la implementación de la competencia emocional como una materia más en el currículo formativo de los futuros profesionales de Trabajo Social, permitiendo una vinculación más directa entre la formación y las necesidades laborales (Salessi y Omar, 2017;Souto et al, 2015).…”
Section: Discusión Y Conclusionesunclassified
See 1 more Smart Citation
“…El entrenamiento en IE debe ser considerado como un elemento transversal en todas las materias de la formación en Trabajo Social. Por ejemplo, las conversaciones sobre las emociones entre estudiantes y profesionales de Trabajo Social con funciones de tutorización de prácticas son una excelente oportunidad pedagógica para la comprensión de los estados emocionales tanto propios como ajenos (i.e., usuarios, compañeros, supervisoras...), la disminución de la sensación de vulnerabilidad y la potenciación del crecimiento profesional y de la felicidad subjetiva (Dore, 2019). Paralelamente, otra línea de actuación se podría centrar en la implementación de la competencia emocional como una materia más en el currículo formativo de los futuros profesionales de Trabajo Social, permitiendo una vinculación más directa entre la formación y las necesidades laborales (Salessi y Omar, 2017;Souto et al, 2015).…”
Section: Discusión Y Conclusionesunclassified
“…Como consecuencia, durante su formación las personas que estudian Trabajo Social deben aprender estrategias que les permitan manejar sus propias emociones para afrontar adecuadamente las exigencias de los usuarios de los servicios sociales (Augusto et al, 2008;Morrison, 2007). Así, destaca el papel de la emoción en el proceso formativo del estudiante de Trabajo Social (Dore, 2019).…”
Section: Introductionunclassified
“…Prior to the aforementioned conversation, my colleague had read my recently published research which identified themes, related to the approach and actions taken by Practice Educators, that helped enable student social workers to talk about emotive practice events (Dore, 2019). From our discussion, two comments stood out: the first related to a sense that there was, potentially, more to be explored in terms of vulnerability (of the participants and their conversations about emotion) and, secondly, they felt that 'I' was not particularly visible within the work.…”
Section: Finding the Way -Parallels With Practicementioning
confidence: 99%
“…This article charts a reflective process that began with a conversation between a colleague and I, about possible topics I might develop as a doctoral study. The discussion focused on one of my earlier pieces of research; exploring how conversations about emotion are enabled with student social workers in supervision (Dore, 2019); causing me to reflect on what I had produced and to engage, more critically, with myself as a researcher. Utilizing a reflective process outlined by Schön (1983), I revisit the original research to retrospectively consider the subject of vulnerability, before going on to explore the biographical aspects of gender and sexuality, subsequently provoked as sources of potential influence on my practice.…”
Section: Introductionmentioning
confidence: 99%
“…Unresolved conflicts with PEs can hinder students' professional development many years later (Baum, 2011). Key to successfully supporting students and enabling them to develop their professional identity is investing time in building and developing a secure, open and honest relationship (Dore, 2019). The practice learning environment should be able to support as well as encourage dialogue and risk taking (Fouché & Lunt, 2010).…”
mentioning
confidence: 99%